2003
DOI: 10.1002/cncr.11809
|View full text |Cite
|
Sign up to set email alerts
|

The percentage of prostate needle biopsy cores with carcinoma from the more involved side of the biopsy as a predictor of prostate specific antigen recurrence after radical prostatectomy

Abstract: BACKGROUNDThe authors previously found that, although the total percentage of prostate needle biopsy cores with carcinoma was a significant predictor of prostate specific antigen (PSA) failure among men undergoing radical prostatectomy (RP), there was a trend toward a lower risk of recurrence in patients with positive bilateral biopsies, suggesting that high‐volume, unilateral disease was a worse predictor of outcome than an equivalent number of positive cores distributed over two lobes. In the current study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 28 publications
0
28
0
3
Order By: Relevance
“…The median (range) number of biopsies taken for each patient was 10.3 (6-24) and the median cores positive for cancer was 2.84 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Unilateral and bilateral nerve-sparing was performed in 70 (14%) and 287 (59%) patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (range) number of biopsies taken for each patient was 10.3 (6-24) and the median cores positive for cancer was 2.84 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Unilateral and bilateral nerve-sparing was performed in 70 (14%) and 287 (59%) patients, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have correlated preoperative clinical and biopsy characteristics with the incidence of ECE and biochemical recurrence [7][8][9][10][11]. Taneja et al [7] reported that the positive predictive value of individual cores for locating ECE was not adequate to guide decisions for nerve-sparing for open RP.…”
Section: Discussionmentioning
confidence: 99%
“…(98). In a concurrent study of the same patients (100), that wasn't a factor, rather the core density, defined as the per cent of total cores positive from each side. With that, having >67% of the cores from the predominant side was the biggest predictor of failure.…”
Section: Modifying Factorsmentioning
confidence: 99%
“…15 The relation between PPC and biochemical relapse free survival (BFS) was explored after ADT 16 , RP [16][17][18] , after WPRT 4,19,20 and brachyterapy. [21][22][23][24] Although the prognostic significance of PPC couldn't be demonstrated in some studies 22 , Yushen et al reported the prognostic value of PPC in intermediate and high risk patients with regard to CSS, BFS and DMFS.…”
Section: Discussionmentioning
confidence: 99%